Interactive H5P Module Enhances Neuroanatomy Learning in Medical Students - Putra, Adi Pratama; Suryada, Kadek Agus (Universitas Multi Data Palembang, 2025)
Neuroanatomy is a challenging subject for medical students due to its complex spatial structures and the integration of multiple functional systems. Digital tools that support active learning, such as the H5P Interactive Book (H5P IB), have the potential to improve student engagement and information retention. This study aims to evaluate the effectiveness and student satisfaction of a neuroanatomy learning module developed using H5P Interactive Book (H5P IB), which features interactive drag-and-drop activities. The module focuses on the neuroanatomy of the central nervous system presented through interactive drag-and-drop quizzes of anatomical images. 160 pre-clinical medical students participated in the study. Learning outcomes were assessed using pre- and post-tests, while student satisfaction was measured using the validated Indonesian version of the Satisfaction Scale for e-Learning Process. Results showed a significant increase in post-test scores compared to pre-test scores (p < 0.01), indicating improved understanding. Student satisfaction was high across all domains, particularly in instructional content and usability. Qualitative feedback further revealed that the drag-and-drop activities helped enhance spatial understanding and overall learning engagement. These findings suggest that the H5P Interactive Book with drag-and-drop features can improve the quality of neuroanatomy learning in medical students.